Relation between birth weight at term and systolic blood pressure in adolescence. - Matthes, J. W. (BMJ Group, 1994)
OBJECTIVE--To examine whether birth weight is related to systolic blood pressure during adolescence. DESIGN--Retrospective (comparative) cohort study. The observers who traced and studied the subjects were unaware of their case-control status. SUBJECTS--330 subjects were born in Cardiff in 1975-7. Cases who were low birth weight at term (< 2500 g) were matched with controls of normal birth weight (3000-3800 g) at term. MAIN OUTCOME MEASURES--Systolic blood pressure measured by random zero sphygmomanometry in the subject's right arm with the subject supine, corrected for size and age. RESULTS--The mean age at examination was 15.7 years. The mean systolic blood pressure of the cases was 105.8 mm Hg and of the controls 107.5 mm Hg. The corrected difference (95% confidence interval) in systolic blood pressure between the cases and controls was 1 mm Hg (-3 to +1 mm Hg; two tailed probability 0.33). CONCLUSION--Systolic blood pressure in adolescents of low birth weight is not significantly different from that of adolescents of normal birth weights.